19.0k views
3 votes
Solve for x:15 = 3(x - 2) + 3

1 Answer

5 votes

hello


15=3(x-2)+3

to solve this problem, let's follow some steps

step 1

multiply through the bracket by it's coefficient


\begin{gathered} 15=3(x-2)+3_{} \\ 15=3x-6+3 \end{gathered}

step 2

add through and collect like terms


\begin{gathered} 15=3x-3 \\ 15+3=3x \\ 18=3x \end{gathered}

step 3

divide both sides by 3


\begin{gathered} 18=3x \\ (18)/(3)=(3x)/(3) \\ x=6 \end{gathered}

x = 6

User Quinton Bernhardt
by
5.5k points